2020
DOI: 10.1088/1361-6463/abb6a9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical nonequilibrium modelling of a free-burning nitrogen arc

Abstract: Thermal and chemical nonequilibrium modelling is performed to investigate the plasma characteristics of a nitrogen arc. The arc plasma is coupled with the electrodes self-consistently in the computational domain. The self-consistent effective binary diffusion coefficient approximation treatment of diffusion and a generalized form of Ohm’s law are incorporated in the model. It is found the electric field has to undergo a reversal in front of the anode to preserve current conservation due to the strong diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Because the spacecharge sheath is considered as an interface between the plasma and electrodes in this study, the space-charge sheath characteristics are revealed by the appropriate boundary conditions imposed at the electrode-plasma interface. This method has already been adopted and validated in the transferred arc simulations, such as short carbon arc and free burning arc [23][24][25][26][27][28]. The flux boundary conditions applied at the interface between the plasma and electrodes are as follows.…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the spacecharge sheath is considered as an interface between the plasma and electrodes in this study, the space-charge sheath characteristics are revealed by the appropriate boundary conditions imposed at the electrode-plasma interface. This method has already been adopted and validated in the transferred arc simulations, such as short carbon arc and free burning arc [23][24][25][26][27][28]. The flux boundary conditions applied at the interface between the plasma and electrodes are as follows.…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…Many numerical methods have been applied to consider the plasma-electrode interactions in arc plasma simulations over the past several decades [18][19][20][21][22][23][24][25][26][27][28][29][30]. The early unified approach with account of arc-electrode interaction consists of an local thermodynamic equilibrium (LTE) bulk plasma and a cathode layer where the diffusion equation is solved to provide ionization layer features [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lun et al [17] developed a model for the vacuum-arc cathode-spot and plasma region to predict the performance of vacuum-arc thrusters operating roughly in the arc current range of 80-300 A. Lun et al [17] reported the conventional-based cathode-spot model with many simplifying assumptions predicted spot radius, surface temperature, electric field, current densities, plasma densities, and energy fluxes. The most recent research conducted in the area has been done by Wang and his co-workers, where the plasma flow feature [18] and species diffusion [19] in a low-power nitrogen-hydrogen arcjet and plasma characteristics of a nitrogen arc [20] were studied by simulation of non-equilibrium arcjets to better understand the arcjet physics. Shen et al [21] studied the starting-up process of arcjet thruster with arc voltage signals.…”
Section: Introductionmentioning
confidence: 99%
“…[10,14] However, the plasma near electrodes obviously deviates from LTE [15][16][17] and LCE, [18,19] thus the thermal and chemical non-equilibrium model is required to study the anode heat transfer of nitrogen arc. In our previous paper, [20] a thermal and chemical nonequilibrium model has been developed for nitrogen arc, but we did not focus on the anode heat transfer characteristics. Moreover, in the previous studies, [21,22] the space charge sheath can significantly affect the plasma energy flux and species flux on the anode surface.…”
Section: Introductionmentioning
confidence: 99%